“I’m Never Going to Be in Phantom of the Opera”: Relational and Emotional Wellbeing of Parkinson’s Carers and Their Partners in and Beyond Dancing - Sundström, Moa; Jola, Corinne (Frontiers in Psychology, 2021)
The caregiving of people who suffer from Parkinson’s predominantly falls on their life partners. Living with and caring for somebody with Parkinson’s can cause a range of emotional, psychological, and financial pressures. Whilst an increasing number of alternative treatments for Parkinson’s is available, such as dancing, the focus is predominantly on the motor and emotional improvements of the person suffering from Parkinson’s. For caregivers, however, dancing can be a double-edged sword: Although dancing can offer an opportunity to enjoy a social event with their partner; attending dance classes puts additional responsibilities on the carer. The present study thus aimed at exploring the experiences of participants with Parkinson’s who attended dance classes as well as the experiences of their care-partners in and around these classes along with their view on everyday life changes experienced since dancing. Six couples were interviewed individually where one partner had Parkinson’s. The interviews were also analyzed separately using inductive thematic analysis. In line with existing programmes that offer dance for people with Parkinson’s, the classes used a mixture of ballroom, ballet, contemporary, and creative dance styles; supported and influenced by an instructors’ extensive knowledge of the abilities and needs of those with Parkinson’s. A recurring challenge for Parkinson’s sufferers relates to “who is in control?” based on the many unknown changes of Parkinson’s; as well as seeing/being seen. Yet frustrations were oftentimes counteracted with humour. Also, when dancing, participants with Parkinson’s reported enjoying playful interactions. Caregivers’ themes focussed on theirs and their partners’ wellbeing regarding social contacts and openness, as well as issues surrounding their responsibilities as carers. Whilst some identified dance movements that help them in everyday tasks, they and their care-partners question the impact of dance on their motor control. Yet, participants unanimously agree that dance provides relevant opportunities for social contact and comparison. Nevertheless, the care-partners’ concerns remain about the burden of increasing responsibility for the wellbeing of both partners but they also reported enjoying dancing with their partner. Experiencing their loved ones as more cheerful after starting dance classes is recognised an important positive and impactful outcome of dancing together.